2011
DOI: 10.1186/1471-2202-12-99
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mineralizing Nestin+ Nkx6.1+ vascular muscular cells from the adult human spinal cord

Abstract: BackgroundThe adult central nervous system (CNS) contains different populations of immature cells that could possibly be used to repair brain and spinal cord lesions. The diversity and the properties of these cells in the human adult CNS remain to be fully explored. We previously isolated Nestin+ Sox2+ neural multipotential cells from the adult human spinal cord using the neurosphere method (i.e. non adherent conditions and defined medium).ResultsHere we report the isolation and long term propagation of anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Overall, these data indicate a neurovasculature origin of these FbCs. In fact, a cell type strongly resembling our FbCs has been described from the adult human spinal cord [48] . Although there are certain differences, such as their inability to form spheres under NPC culture conditions, when cultured under serum-containing conditions, these spinal cord cells behaved like our FbCs in that they proliferated as an adherent monolayer and expressed Nestin, Sox2, PDGFRβ and α-SMA.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Overall, these data indicate a neurovasculature origin of these FbCs. In fact, a cell type strongly resembling our FbCs has been described from the adult human spinal cord [48] . Although there are certain differences, such as their inability to form spheres under NPC culture conditions, when cultured under serum-containing conditions, these spinal cord cells behaved like our FbCs in that they proliferated as an adherent monolayer and expressed Nestin, Sox2, PDGFRβ and α-SMA.…”
Section: Discussionsupporting
confidence: 66%
“…Although there are certain differences, such as their inability to form spheres under NPC culture conditions, when cultured under serum-containing conditions, these spinal cord cells behaved like our FbCs in that they proliferated as an adherent monolayer and expressed Nestin, Sox2, PDGFRβ and α-SMA. Furthermore, they also found these antigens to be localized to the blood vessels of the spinal cord [48] . Neurovasculature contamination of brain tissue cultures is unavoidable and when taken together with the above results, it appears our brain-derived FbCs are likely to be of neurovascular origin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Only one group has been able to perform in vitro assays with human ependymal cells; they found that human ependymal neurospheres may give rise to cells expressing glial and neuronal markers (GFAP, GABA, 5-HT), but cannot be passaged (Dromard et al, 2008;Hugnot and Franzen, 2011). Moreover, when cultured in adherent conditions, these cells can be passaged, but produce cells with a molecular profile compatible with mesodermal cell types (Mamaeva et al, 2011). Together, the morphological, molecular, and functional data may question the role of adult spinal cord ependyma as a neurogenic niche in adult humans, but more functional studies are needed to fully support this claim.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, its expression correlates with high FLAIR volumes and the mesenchymal subtypes of GBM. Further accuracy in the overall survival is provided by the overexpression of genes associated with proliferation ( AURKA [ 37 ], BUB1 [ 38 ], BUB1B [ 38 ], DLG7/DLGAP5 [ 39 ], FOXM1 [ 40 ], KI67 [ 13 ], NEK2 [ 41 ], PLK1 [ 42 ]), apoptosis ( BIRC5/SURVIVIN [ 12 ]) and vasculature ( COL1A1 [ 43 ], HSPG2 [ 44 ], JAG1 [ 45 ], NKX6.1 [ 46 ], TNC [ 47 ]). Their overexpression in poor-prognosis patients is consistent with the fact that enhanced proliferation, apoptosis inhibition and angiogenesis are hallmarks of disease progression in many cancers [48].…”
Section: Discussionmentioning
confidence: 99%